X(X-16)-63=0

Simple and best practice solution for X(X-16)-63=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X(X-16)-63=0 equation:


Simplifying
X(X + -16) + -63 = 0

Reorder the terms:
X(-16 + X) + -63 = 0
(-16 * X + X * X) + -63 = 0
(-16X + X2) + -63 = 0

Reorder the terms:
-63 + -16X + X2 = 0

Solving
-63 + -16X + X2 = 0

Solving for variable 'X'.

Begin completing the square.

Move the constant term to the right:

Add '63' to each side of the equation.
-63 + -16X + 63 + X2 = 0 + 63

Reorder the terms:
-63 + 63 + -16X + X2 = 0 + 63

Combine like terms: -63 + 63 = 0
0 + -16X + X2 = 0 + 63
-16X + X2 = 0 + 63

Combine like terms: 0 + 63 = 63
-16X + X2 = 63

The X term is -16X.  Take half its coefficient (-8).
Square it (64) and add it to both sides.

Add '64' to each side of the equation.
-16X + 64 + X2 = 63 + 64

Reorder the terms:
64 + -16X + X2 = 63 + 64

Combine like terms: 63 + 64 = 127
64 + -16X + X2 = 127

Factor a perfect square on the left side:
(X + -8)(X + -8) = 127

Calculate the square root of the right side: 11.26942767

Break this problem into two subproblems by setting 
(X + -8) equal to 11.26942767 and -11.26942767.

Subproblem 1

X + -8 = 11.26942767 Simplifying X + -8 = 11.26942767 Reorder the terms: -8 + X = 11.26942767 Solving -8 + X = 11.26942767 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + X = 11.26942767 + 8 Combine like terms: -8 + 8 = 0 0 + X = 11.26942767 + 8 X = 11.26942767 + 8 Combine like terms: 11.26942767 + 8 = 19.26942767 X = 19.26942767 Simplifying X = 19.26942767

Subproblem 2

X + -8 = -11.26942767 Simplifying X + -8 = -11.26942767 Reorder the terms: -8 + X = -11.26942767 Solving -8 + X = -11.26942767 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + X = -11.26942767 + 8 Combine like terms: -8 + 8 = 0 0 + X = -11.26942767 + 8 X = -11.26942767 + 8 Combine like terms: -11.26942767 + 8 = -3.26942767 X = -3.26942767 Simplifying X = -3.26942767

Solution

The solution to the problem is based on the solutions from the subproblems. X = {19.26942767, -3.26942767}

See similar equations:

| 2x+6x-80=112 | | 92+78x= | | 0.5x+2.1=0.9x-0.3 | | B-7+2b=31 | | .50x+.25(60)=.25(82) | | 1/2=m-1/8 | | 49+3x= | | 2(5x+20)-4x= | | 3x^2y+6xy+9xy^2=0 | | 2-3x+y+10=0 | | -2x-7=-3x-9 | | -1/4x+5=x+2 | | -.4x+.9x+4=-6 | | 14x+3=3(4x-2)+2x+9 | | 15u^5+18u^3=0 | | 2.3=4.1-0.6x | | 12+21=w-27 | | Y=-16x^2-22x+40 | | .79saw=34 | | -2(1+5a)=-6(3+a) | | -8(5)+10y=-20 | | 22=16+f | | 0.5x+0.04= | | -35v+25=-9v-90 | | 4000(0.20-x)=x | | -7(z+6)=-70 | | 4-5x=-59 | | 6(5)-10y=10 | | 43-7x= | | .79saw=24 | | 5x+7-4x=15 | | 5xsquared-20=0 |

Equations solver categories